Self-efficacy and Academic Stress in Senior High School Students Plus Assa'adah, Banten - Zahrotusyifa, Laila; Samara, Tjam Diana (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: The National Education System Law No. 20/2003 states that education aims to develop student potential. A religious learning approach is one of many methods to develop student potential. High School Plus Assa'adah uses this approach. However, this approach can increase students' academic stress due to busy schedules and tasks. Low self-efficacy can cause students to lack confidence in facing these tasks. This study aims to determine the relationship between self-efficacy and academic stress in high school students. Method: This study used a cross-sectional design with observational analytics. A total of 90 respondents were studied with an age range of 14 - 17 years. The sampling technique was consecutive non-random sampling, with the inclusion criteria being students who were in eleventh-grade and physically filled out the questionnaire during the study. Exclusion criteria were students who were taking antidepressant and antianxiety drugs. Assessment of self-efficacy and academic stress using the General Self-Efficacy Scale and Student-Life Stress Inventory, the validity and variability tests of which are based on previous research. Chi-Square test was used to analyze the data with a significance level (p) <0.05. Result: Most respondents were male (52.2%), and the highest age was 16 (64.4%). Most students had moderate self-efficacy (65.6%), while the others had moderate academic stress (57.8%). The Chi-Square test showed no relationship between self-efficacy and academic stress (p=0.277). Conclusion: Self-efficacy was not associated with academic stress in high school plus students. It is necessary to look for other factors besides self-efficacy that can cause academic stress so that academic results can be improved.